UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD - Widiyanto, Rohmat; Hamidah, Mida (ATTA`DIB, 2016)
This research is motivated by the findings in the learning process in the field prior to use cooperative learning model Student Achievement Teams Division (STAD). Problems found that the average results of student learning and mastery learning in social studies material on the struggle against the occupiers has not reached the set value (KKM). The method used is a Class Action Research model of Taggart Kemmis and consists of three cycles. This research was conducted in class V SDN Cikahuripan the number of students as many as 41 people. Data collection technique used qualitative (observation sheet) and quantitative (data processing using a specific formula). Based on the research results, we concluded that the application by using cooperative learning model student achievement teams division (STAD) has been fulfilled properly. Thus, increase student learning outcomes. Moreover, in the process of becoming more active student learning, students are able to learn the group well and learning even more fun.